If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13y + -26 = 7y + 22 Reorder the terms: -26 + -13y = 7y + 22 Reorder the terms: -26 + -13y = 22 + 7y Solving -26 + -13y = 22 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -26 + -13y + -7y = 22 + 7y + -7y Combine like terms: -13y + -7y = -20y -26 + -20y = 22 + 7y + -7y Combine like terms: 7y + -7y = 0 -26 + -20y = 22 + 0 -26 + -20y = 22 Add '26' to each side of the equation. -26 + 26 + -20y = 22 + 26 Combine like terms: -26 + 26 = 0 0 + -20y = 22 + 26 -20y = 22 + 26 Combine like terms: 22 + 26 = 48 -20y = 48 Divide each side by '-20'. y = -2.4 Simplifying y = -2.4
| 8x+20=5x+35 | | 3x-7y+6z=5 | | X^8=1/12 | | 16/5x=1/10 | | x-5y=-2 | | 9=2w+5 | | -8n-3=-27 | | 3(3x-3)-28=4x-2 | | 3/2*(1-4x)^1/2=-30 | | (((3x-1/4)^2))^4 | | 5x-12=10-6x | | FxD=F | | 11/2*31/2*23/4 | | 4=-6+x | | A+C=A | | 6+9=3x | | -30=3r | | 38=7b+10 | | 2(x-1)=10(1-x)+6 | | 3xy+4xy-xy= | | 4x+29=5-8(x+6) | | 25x^2-36=o | | 6(5y-1)=-2y-38 | | 2+4r=5+4r | | X*7-4x=19-2x | | 90=-6(1+8q) | | 1-5m+3m=3 | | -x^3-6x^2+36x+216=0 | | -8-3(w+13)=4(w+11)-7w | | 15=5/6c | | -2(3x+1)-6x+7= | | 3x-2=55 |